Bipolar resistive switching of bi-layered Pt/Ta2O5/TaOx/Pt RRAM : physics-based modelling, circuit design and testing - Hatem, Firas Odai (2017)
Over the last few years, the non-volatile memories (NVM) have been dominating the research of the storage elements. The resistance random-access memory (RRAM) and the memristor that employs the resistive switching (RS) mechanism appear to be potential candidates for NVM. Among the RS materials that were reported is the TaOx which showed surprising RS performance. This oxide material has been widely used to construct a metal-insulator-semiconductor-metal (MISM) RRAM which can be referred to as bi-layered RRAM. This bi-layered RRAM consists of TaOx as a bulk material and Ta2O5 as an insulator layer, sandwiched between two platinum electrodes to form Pt/Ta2O5/TaOx/Pt RRAM. However, a physics-based mathematical model of this RRAM is required to further study the detailed physics behind its conduction mechanism and the RS process. In addition to the mathematical model, a SPICE model is also required to understand the behaviour of this bi-layered RRAM device when integrated in memory design for the future generation storage devices or when used in RRAM-based circuit applications. This doctoral research presents novel mathematical and SPICE models of a bipolar resistive switching (BRS) of the Pt/Ta2O5/TaOx/Pt bi-layered RRAM. For this purpose, MATLAB and LTSPICE are used to design the mathematical and the SPICE bi-layered RRAM models, respectively, and the obtained simulation results for both models are compared with the experimental data from SAMSUNG labs. The novelty of the mathematical model lies in incorporating the tunnelling probability factor (TPF) between the semiconductor and the metal layers and therefore, demonstrating its effect on the conduction mechanism. In addition, the effect of continuous variation of the interface traps densities and the ideality factor during BRS is modelled using the semiconductor properties and the characteristics of the metal-insulator-semiconductor (MIS) system. Thus, the model emphasizes the dependency of the device current on the physical characteristics of the insulator layer. Moreover, the electric field equation for the active region is derived for the MISM structure which is used together with Mott and Gurney rigid point-ion model and Joule heating effect to model the oxygen ion migration mechanism. Finally, the model also demonstrates the self-limiting growth of the doped region. The proposed SPICE model emphasizes the impact of the change in the switching layer thickness on the device behaviour at low resistance state (LRS), high resistance state (HRS), and the transitional period. The validity of the SPICE model is verified through using three different sets of experimental data from Pt/Ta2O5/TaOx/Pt RRAM with switching layer thickness smaller than 5 nm. The SPICE model reproduced all the major features from the experimental results for the SET and RESET processes and also the asymmetric and the symmetric characteristics in HRS and LRS, respectively. The SPICE model matches the measured experimental results with an average error of < 11%. It also showed stable behaviour for its HRS and LRS regions under different types of input signals. The model is parameterized in order to fit into Ta2O5/TaOx RRAM devices with switching layer thickness smaller than 5 nm, thus, facilitating the model usage. The SPICE model can be included in the SPICE-compatible circuit simulation and is suitable for the exploration of the Ta2O5/TaOx bi-layered RRAM device performance at circuit level. At the end of the research, a metal-insulator-metal (MIM) RRAM SPICE model of Ta/TaOx/Pt is developed which can be used in the future work to compare between the MISM and MIM TaOx-based RRAM devices.